Design for information an introduction to the histories, theories, and best practices behind effective information visualizations - Meirelles, Isabel (Rockport Publishers, 2013)
"This book is designed to help you foster the development of a repertoire of existing methods and concepts to help you overcome design problems."--Provided by publisher.